Pengaruh Citra Merek, Harga, Promosi, Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Myrepublic Di Kabupaten Jember - Imel Triana Ghausillah; Yuniorita Indah Handayani; Haifa Haifa (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the effect of brand image, price, promotion, product quality, and service quality on MyRepublic customer satisfaction in Jember Regency. A quantitative approach was employed using purposive sampling, involving 100 active MyRepublic customers as respondents. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, the coefficient of determination (R²), t-test, and F-test with the assistance of SPSS version 20. The findings indicate that brand image, product quality, and service quality have a positive and significant partial effect on customer satisfaction, whereas price and promotion do not have a significant effect. Simultaneously, all independent variables significantly influence customer satisfaction. These findings suggest that MyRepublic customers place greater emphasis on product quality, service quality, and brand image than on price and promotional factors when evaluating their satisfaction. The results are expected to provide useful insights for the company in developing marketing strategies focused on improving service quality and strengthening brand image.